Pacific Grove Cottage. - Richard L. Allman:::Creator::::::::::::
The Eleventh Street Steinbeck cottage showing the rear garden and entry. Built in 1903 by John Ernest Steinbeck, Sr., John's father, this house was used by the Steinbeck family as a summer vacation home. John and Carol Steinbeck lived in this cottage periodically from 1930-1936. RESTRICTED USE